Assessing the Preferences for Criteria in Multi-Criteria Decision Analysis in Treatments for Rare Diseases - Schey, Carina; Postma, Maarten Jacobus; Krabbe, Paul F. M.; Topachevskyi, Olekdandr; Volovyk, Andrew; Connolly, Mark (Frontiers in Public Health, 2020)
Background: Increasingly, multi-criteria decision analysis has gained importance as a method by which to assess the value of orphan drugs. However, very little attention has been given to the weight (relative preferences) of the individual criteria used in a framework. Aims: This study sought to gain an understanding of the preferential weights that should be allocated in a multi-criteria decision analysis framework for orphan drugs, from a multi-stakeholder perspective. Method: Using key MCDA criteria for orphan drugs reported in the literature, we developed an interactive web-based survey tool to capture preferences for different criteria from a general stakeholder sample who were requested to assign weights from a reimbursement perspective. Each criterion could be assigned a weight on a sliding scale from 0 to 100% as long as the sum of all the criteria was 100%. We subsequently used the interactive tool with an expert focus group, followed up with a group discussion regarding each criterion and their perspectives on the weight that each criterion should be allocated when assessing an orphan drug. The expert focus group participants were then able to adjust their weights, if the group discussion had changed their perspectives. Results: The interactive tool was completed by 120 general stakeholder sample from a wide range of countries and professional backgrounds and an expert focus group of ten members. The results showed the differences in perspectives on the importance of criteria. Both groups considered Treatment efficacy to be the most important criterion. The general stakeholder sample weighted Treatment safety at 12.03% compared to the expert focus group's average of 20%. The results also demonstrated the value of the group discussion, which provided additional insights into the perspectives on the importance of criteria in assessing orphan drugs. Conclusion: This study aimed to contribute to the important aspect of preferences for different criteria in MCDA. This study sheds light on the important aspect of the preferences of the different criteria. All respondents agreed on the relative importance of Treatment efficacy and Treatment safety, criteria that are captured in conventional cost-effectiveness studies, but they also expressed the view that in addition to those, several disease-related and drug-related criteria should be included in MCDA frameworks for assessing orphan drugs.